EXPLORING AND TRANSLATING “YONG DOLLAH” LOCAL MALAY STORIES INTO ENGLISH FOR SENIOR HIGH SCHOOL ELT MATERIALS IN BENGKALIS - Boni Saputra; Rionaldi Rionaldi; Aswandi Aswandi (UAD TEFL International Conference)
Malay story “Yong Dollah” is one of cultural heritage in the form of oral literature in Bengkalis. This story has been very popular and often been told to children, teenagers or even adults in certain occasion like at night or free time. It has been told throughout generations in the life of Malay people in Bengkalis. Yong Dollah is a character created by a man named Abdullah bin Endong, Bengkalis Malay artist. In his entire life, he liked to tell stories that mostly came from his imagination to entertain people. The contents of his stories were often related to his daily life, adventure and often contained certain moral value for audience. The popularity of the stories could be used as learning resource text and media to teach English for senior high school students. However, English version of these stories had never been made before. The exploration and translation of the original stories into English were done to meet the need of learning. Method of translating used in this study was adaptation where intercultural differences between original text from source language (Bahasa Melayu) and target language (English) were adjusted to convey the original meaning from the content of the language. Results of the translation were set of translated stories of Yong Dollah. These Stories can be used by teacher in teaching English for senior high school students. In addition, this study could also be used as alternative entertainment and could help to preserve cultural heritage of Malay people.